Identification of microsatellite loci and examination of genetic structure for the endangered springsnails Juturnia kosteri and Pyrgulopsis roswellensis in the Chihuahuan Desert. Issue 4 (24th February 2016) - Holste, Danielle R.; Inoue, Kentaro; Lang, Brian K.; Berg, David J.
Abstract: Desert spring ecosystems harbour many endemic species that are threatened with extinction owing to human activities. Springsnails (superfamily Truncatelloidea) are among the most diverse freshwater snail groups in desert springs of western North America. They occupy geographically narrow ranges, often consisting of a single spring or spring complex. Microsatellite markers were developed via high‐throughput de novo sequencing for two endangered springsnail species, Juturnia kosteri and Pyrgulopsis roswellensis, endemic to springs on Bitter Lake National Wildlife Refuge (BLNWR) near Roswell, New Mexico, USA. Genetic diversity, population structure, effective population size ( N e ), and historic demography were assessed in two populations for each species. A large number of putative markers were identified, of which 14 loci for J. kosteri and 18 loci for P. roswellensis showed polymorphism. Genetic diversity and N e were greater in P. roswellensis than J. kosteri . Significant genetic differentiation ( F ST  = 0.187–0.288) was found among populations for both species, indicating currently limited gene flow. Neither species showed signs of recent population bottlenecks. Analyses with microsatellite markers revealed fine‐scale population genetic structure in both species, unlike a previous study using mitochondrial DNA sequences. Although these species co‐occur on BLNWR, slightly different genetic characteristics between them suggest that they may have different evolutionary and demographic histories. Small N e relative to census size indicates strong genetic drift in these populations. Future efforts should be directed to identifying causes of such strong drift. Because there are limited numbers of microsatellite markers available for springsnails, the markers identified in this study should be useful for congeners via cross‐species amplification. Understanding current genetic variation and structure of these species is not only required for species recovery, but will also be useful for comparisons among many aquatic organisms endemic to springs of western North America. Copyright © 2016 John Wiley & Sons, Ltd.